Loss of HES-1 Expression Predicts a Poor Prognosis for Small Intestinal Adenocarcinoma Patients - Kim, Jeong Won; Jun, Sun-Young; Ylaya, Kris; Chang, Hee-Kyung; Oh, Young-Ha; Hong, Seung-Mo; Chung, Joon-Yong; Hewitt, Stephen M. (Frontiers in Oncology, 2020)
Objective: Hairy and enhancer of split-1 (HES-1), which is a downstream target of the Notch signaling pathway, has been linked to KRAS mutations. HES-1 has been proposed as harboring oncogenic activity in colorectal cancer but has not been investigated in adenocarcinoma of the small intestine, where the drivers of oncogenesis are not as well understood. Materials and Methods: To investigate the clinicopathologic and prognostic implications of HES-1, HES-1 immunohistochemical expression was analyzed in digital images along with clinicopathological variables, including survival and KRAS genotype, in 185 small intestinal adenocarcinomas. Results: The loss of HES-1 expression (HES-1Loss) was observed in 38.4% (71/185) of the patients, and was associated with higher pT category (P = 0.018), pancreatic invasion (P = 0.005), high grade (P =0.043), and non-tubular histology (P = 0.004). Specifically, in tumors with mutant KRAS (KRASMT), HES-1Loss was related to proximal location (P = 0.024), high T and N categories (P = 0.005 and P = 0.047, respectively), and pancreatic invasion (P = 0.004). Patients with HES-1Loss showed worse overall survival compared to those with intact HES-1 (HES-1Intact) (P = 0.013). Patients with HES-1Loss/KRASMT (median, 17.3 months) had significantly worse outcomes than those with HES-1Intact/KRASWT (39.9 months), HES-1Intact/KRASMT (47.6 month), and HES-1Loss/KRASWT (36.2 months) (P = 0.010). By multivariate analysis, HES-1Loss (hazard ratio = 1.55, 95% confidence interval (CI), 1.07 – 2.26; P = 0.022) remained an independent prognostic factor. Conclusion: HES-1 expression can be used as a potential prognostic marker and may aid in the management of patients with small intestinal adenocarcinomas.